PERLINDUNGAN HUKUM TERHADAP ANAK - Kusumo, Bambang Ali (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
Children are an asset of the nation that needs to be well prepared, because the future of this country or nation is determined by the child or the young generation. Given this, then the legal protection of children is very important to do. Areas that need protection for children are religious, health, education, social and special fields. In order to realize or realize the protection of children, the Indonesian Child Protection Commission was established. The Commission has the duty to supervise the implementation of the protection and fulfillment of the Rights of the Child; provide input and suggestions in the formulation of policies on the implementation of Child Protection; Collect data and information on Child Protection; receiving and conducting a review of public complaints regarding violations of the Rights of the Child; Mediate the dispute over Child Rights violations; Cooperate with institutions established by the Community in the field of Child Protection, and report to the authorities on the alleged violation of this Law. " Keyword: Protection, child, law.